A National Aged Care Infection and Antimicrobial Use Survey: A Three-Year Report. (October 2020) - Bennett, Noleen; Buising, Kirsty; Ingram, Robyn
Abstract : Background: Australia has 2, 700 aged-care homes and 180 multipurpose services. The annual Aged Care National Antimicrobial Prescribing Survey (AC NAPS), first pilot tested in 2015, is a surveillance tool that can be used in these facilities to monitor infections and antimicrobial use. It assists in identifying priorities for local and national infection control and antimicrobial stewardship interventions. Methods: Nurses or pharmacists collect point prevalence data using standardized data collection forms: (1) A facility form, completed by each participating facility, includes resident-level data fields (eg, number of residents present on the survey day). (2) An infection form is completed for residents with signs and/or symptoms of infection. (3) An antimicrobial form is completed for residents who are prescribed an antimicrobial. Results: Regarding prevalence, for those 31 facilities that participated annually, there was no significant change in either prevalence rate (Table 1). Regarding priority areas for improvement (2018 data only), 64.6% of prescriptions were for residents who did not have signs and/or symptoms of a suspected infection in the week prior to the antimicrobial start date. The most common clinical indications for prescriptions were skin soft-tissue and mucosal infection (18.3%), cystitis (16.0%) and pneumonia (9.4%). Cefalexin (20.3%), clotrimazole (19.0%), and chloramphenicol (7.0%) were the most commonly prescribed antimicrobials. Review or stop dates were not documented for 58.9% of prescriptions. Only 39.2% of antimicrobials were prescribed in the 7 days prior to the survey day; 28.3% were prescribed >6 months prior. Furthermore, 36.3% of all prescriptions were for topical application. In addition, 19.0% of antimicrobials were prescribed for PRN (as needed) administration; most (94.4%) of these were for topical antimicrobials, most commonly clotrimazole (65.4%). Conclusions: The AC NAPS has identified infections and consistent patterns of antimicrobial use that may adversely affect the safety of care for Australian aged-care residents. Interventions are now being developed, implemented, and evaluated to address identified 'priority areas for improvement.' Funding: None Disclosures: None